2002
DOI: 10.1034/j.1399-0012.2002.01128.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver preservation with HTK: salutary effect of hypothermic aerobiosis by either gaseous oxygen or machine perfusion

Abstract: The aim of the present study was to improve the viability of marginal livers from non-heart beating donors upon cold preservation using two different techniques for the provision of tissue aerobiosis. Livers from male Wistar rats (250-300 g bw) were harvested after 60 min of cardiac arrest, flushed via the portal vein with 20 mL of heparinized Ringer's solution and 60 mL of histidine-tryptophan-ketoglutarate (HTK) preservation solution. Control livers were then stored submerged in HTK for 24 h at 4 degrees C w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 28 publications
3
16
0
Order By: Relevance
“…Consistent with reports from previous studies and that from our laboratory [11,22,23], it was found that HMP significantly improves hepatic parenchymal enzyme release and functional recovery upon reperfusion. Beyond this, we could provide evidence that oxygenation during ex vivo storage by machine perfusion with either preservation medium significantly improved mitochondrial integrity, compared to simple CS, and largely attenuated cleavage of caspase 9, hallmark of the initiation of the intrinsic pathway of apoptosis.…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with reports from previous studies and that from our laboratory [11,22,23], it was found that HMP significantly improves hepatic parenchymal enzyme release and functional recovery upon reperfusion. Beyond this, we could provide evidence that oxygenation during ex vivo storage by machine perfusion with either preservation medium significantly improved mitochondrial integrity, compared to simple CS, and largely attenuated cleavage of caspase 9, hallmark of the initiation of the intrinsic pathway of apoptosis.…”
Section: Discussionsupporting
confidence: 82%
“…Animal liver transplantation models have successfully used HMP with donation after cardiac death (DCD) livers. (8)(9)(10)(11) The major drawback of HMP is that prolonged perfusion during hypothermia may injure the sinusoidal endothelial cells due to increased vascular resistance and imposed shear stress, (12,13) so only short, 1-3 hour perfusion durations are feasible. In addition, HMP seems to offer reduced protection with marginal grafts.…”
mentioning
confidence: 99%
“…Therefore, over the past years, aerobic preservation methods were investigated as an alternative to the conventional cold storage (CS). It was demonstrated that aerobic preservation via continuous oxygenated machine perfusion (MP) or venous oxygen persufflation (VSOP) are superior to classical CS in many aspects [4][5][6][7][8][9][10]. The major drawback of MP lies in its comparatively cumbersome applicability, the necessity of being timely available at the place of organ retrieval and the need of continuous surveillance thereafter.…”
Section: Introductionmentioning
confidence: 98%